Membangun Kesehatan Mental Generasi Alpha: Urgensi Konseling dalam Mengatasi Tantangan Bullying di Era Sosial Media Melalui Komunikasi Empati - Harahap, Fitri Amelia; Sampurna, Ahmad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research aims to determine the urgency of counseling in overcoming the challenges of bullying in the era of social media through empathetic communication. This research is a qualitative-descriptive study with a phenomenological approach to observe and describe natural phenomena that occur in the alpha generation in the social media era. Research data was obtained from bullying cases on social media, as well as from journal articles and other relevant literature. Analysis of this research data involves data reduction, data presentation, and conclusion. The validity of the research data was carried out using triangulation testing. The results of this research show that building the mental health of the Alpha generation through counseling is essential in the modern era filled with technology. Counseling creates a safe space to share experiences and feelings, helping them manage technological stress and social pressure. Addressing bullying in the age of social media requires empathetic communication, approaching the perpetrator with tact, providing positive support, and creating a safe place to talk. This can form a culture that is friendly, and supportive, and teaches the values of diversity and respect for others. Counseling and empathetic communication are not only solutions to psychological problems and bullying, but also a strong foundation for the mental and emotional well-being of the Alpha generation in an ever-changing world.